Implementation of Virtual Clashroom: Connecting Teachers and Students Online for Effective Distance Learning - Pardede, Mahadi; Suprayitno, Degdo; Tari, Tari; Cahyono, Bambang; Musmulyadin, Musmulyadin (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2024)
The global pandemic has pushed educational communities around the world to look for innovative solutions to make distance learning effective. One of the emerging solutions is to use Virtual Clashroom, a concept that combines cutting-edge video conferencing technology with student-focused interactions. This research discusses the application of Virtual Clashroom as a solution to connect teachers and students online in distance education. Virtual Clashroom provides an interactive platform that allows teachers to teach in a more interesting and interesting way. With features like digital whiteboards, screen sharing, and interactive chat, teachers can facilitate active and collaborative learning. Students can ask questions, participate in discussions, and collaborate with other students in a safe virtual environment. This research also evaluates the effectiveness of Virtual Clashroom in increasing student engagement, subject understanding, and teacher-student interactions. The results show that Virtual Clashroom can create a more interesting and effective distance learning experience than conventional methods. Students reported high levels of satisfaction in using the platform, while teachers felt they could teach more effectively in a virtual environment. The Virtual Clashroom application opens up new opportunities in the world of education, especially during emergency situations such as a pandemic. By utilizing this technology, distance learning can become more interactive, inclusive and effective. This study provides valuable information about how Virtual Clashroom can be the right solution to improve the quality of education in the future. The method used in this research is a quantitative method. Researchers conducted a survey using a Google form consisting of 15 statements related to the title of the research. The limitation of this research is that the researcher only conducted research in schools and the researcher did not conduct research directly in schools but shared a survey link on a Google form containing a statement about Implementing Virtual Clashroom: Connecting Teachers and Students Online for Effective Distance Learning.